2013
DOI: 10.1099/vir.0.055459-0
|View full text |Cite
|
Sign up to set email alerts
|

African, Amerindian and European hepatitis B virus strains circulate on the Caribbean Island of Martinique

Abstract: Ten Hepatitis B virus (HBV) genotypes, as well as numerous subgenotypes, have been described in well-characterized ethnogeographical populations. Martinique has been at a crossroads between Africa, Europe, India and the Americas because of the slave trade (17th-19th centuries), followed by an important immigration of Indian and West African workers. In this work, we aimed to study the molecular epidemiology of HBV infection in Martinique according to this unique settlement pattern. To that end, blood samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
1
19
0
5
Order By: Relevance
“…One clade is mainly ‘African’ and includes isolates from southern, eastern and central Africa, while the other, comprising isolates from Asia and Somalia, has been called ‘Asian’ [45][47] or ‘Afro-Asian’ [48]. Recently, the term ‘Asian-American’ has also been used to design this latter clade, based on phylogenetic analyses that included HBV/A1 isolates from Caribbean islands and a restricted number of South American strains [19], [31]. The ‘Asian-American’ clade would have originated in the nineteenth century when African slaves were exported from Mozambique to Central and South America, the islands of the Indian Ocean, and India.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One clade is mainly ‘African’ and includes isolates from southern, eastern and central Africa, while the other, comprising isolates from Asia and Somalia, has been called ‘Asian’ [45][47] or ‘Afro-Asian’ [48]. Recently, the term ‘Asian-American’ has also been used to design this latter clade, based on phylogenetic analyses that included HBV/A1 isolates from Caribbean islands and a restricted number of South American strains [19], [31]. The ‘Asian-American’ clade would have originated in the nineteenth century when African slaves were exported from Mozambique to Central and South America, the islands of the Indian Ocean, and India.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the circulation of HBV genotypes A, D, and F reflects the ancestral descent of the Brazilian population [23]. The origin of the Brazilian population can be traced from three main sources, namely the Amerindians, who are mainly HBV/F carriers [28], [29], the European colonizers, responsible for the entry of genotypes A2 and D into Latin America [30], [31], and the African slaves, who would have been carriers of HBV/A1 when they arrived in Brazil between the 16 th and the 19 th century. The proposal that subgenotype A1 was introduced into Brazil by the arrival of slaves [23], [24] has been reinforced by the observations that (i) HBV/A1 is almost the exclusive subgenotype found in semi-isolated Afro-descendant communities [32]–, and (ii) Blacks and Mulattos (mixed descent) are more frequently infected with subgenotype A1 than caucasians, whereas the contrary is true for genotype D [30].…”
Section: Introductionmentioning
confidence: 99%
“…), включа-ющий рекомендованный для генотипирования ВГВ регион Pre-S1/Pre-S2/S протяженностью 1169 п.о., область 2848-3182...1-835 нт, согласно представленному в международной базе данных GenBank изоляту Mart-B47 (HE974377.1) [10].…”
Section: материалы и методыunclassified
“…), включающий рекомендованный для гено-типирования ВГВ регион Pre-S1/Pre-S2/S про-тяженностью 1169 п.о., область 2848-3182...1-835 нт, согласно представленному в междуна-родной базе данных GenBank изоляту Mart-B47 (HE974377.1) [10].…”
Section: материалы и методыunclassified